Historical and tactical development of the 6:0 defence system in handball - Espina-Agullo, J. J.; Jove-Tossi, M. A. (Journal of Human Sport & Exercise, 2012)
We start our study by describing the basic 6:0 Defence System in handball to identify the problem both conceptually and tactically. We then establish the origins of this system and provide a timeline that identifies when it came into being and how it developed from then on. The anthropometric, physical, technical and technical factors mentioned above have played a key role in said development. Finally, we will state the conclusions reached in the study.